Style changes on presentation of news services: Lorenzo Milá and Matías Prats - García González, Aurora; Román Portas, Mercedes; Rodríguez Valcárcel, Marta (Universidad de Chile. Instituto de la Comunicación e Imagen, 2017)
This article studies the change in the style of the presentation of the information in Spain from the incorporation of two presenters who were catalysts for the establishment of a new style of presenting the information: Matías Prats and Lorenzo Milá. To that end, the academic literature has been revised, as well as the newspaper archives of the newspapers El País, La Vanguardia and ABC, and the documentary fund of TVE has been accessed through the company’s website. Each presenters, belongs at the time of the study, belongs to a public and private television channel. The work is part of a systematized historical study that will try to establish patterns, detect changes and divergences between theory and practice and analyze forms of content continuity and the appearance of new styles between 1990 and 2010.